Effect of sulfate mine water on the durability of filling paste. Issue 13 (21st October 2018) - Liu, Yin; Lu, Yao; Wang, Changxiang; Cui, Boqiang; Guo, Hao; Li, Hao; Guo, Yalan
ABSTRACT: In order to research the influence of high-sulfate mine water on filling paste, the macroscopic and microstructural changes of the filling paste in the sulfate environment were analyzed by uniaxial compression tests, X-ray diffraction (XRD) and scanning electron microscope (SEM). The mechanism of deterioration and cracking was discussed. The experimental results show that there are numerous gelling materials in the specimen during the curing period, which can increase the strength of the specimen. After cured paste specimen was soaked in sulfate solution for less than 90 days, the hydration reaction continued, the gelling substance was produced and the sulfate formed the filling material, which caused the compressive strength of the paste specimen to increase with the increase of immersion age. The compressive strength of the specimen was higher than that of the specimen soaked in water. The gypsum and ettringite formed in the specimen filled the void of the specimen after immersion in sulfate solution for more than 90 days, destroying the original cementing structure of the specimen, and the compressive strength of the specimen began to decrease with the increase of the immersion age. The compressive strength of the cured paste specimen after being soaked in sulfate solution for more than 180 days was lower than that of the specimen soaked in clear water and the larger the solution concentration, the longer the immersion time, the smaller the compressive strength of the specimen, and the more significant the deterioration effect is.